A feasibility study on establishing and indexing society - Florese, August Emmanuel N. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
This study is an inquiry into the feasibility of establishing an indexing society. Because of the stagnation of indexing research compared to the growth of indexing as a profession, this paper proposes creating an indexing society as a solution to this problem. The goal of the paper is to assess the viability of indexing from an asset-side perspective. To do so, it measures three things: demand for indexing work, membership clamor, and inter-associational support through creating projections on the demand for indexers and indexing, conducting a survey on indexers in Metro Manila, and conducting interviews with key staff of major librarianship organizations respectively. Due to the paucity of information on demand and the exigencies of research, the information gathered was incomplete. However, because membership clamor was strong and inter-associational support considerable, this paper can conclude at least a partial feasibility. However, further study will be needed to shore up the shortcomings of this publications.